Video field production and editing - Compesi, Ronald J. 1949- (Routledge, an imprint of the Taylor & Francis Group, 2019)
"In the eighth, revised edition of this book, Ronald J. Compesi offers a comprehensive and in-depth introduction to the aesthetics and techniques of small-scale, single-camera video production in field environments, from planning through postproduction, in a range of different programming formats. Written in an accessible, student-friendly style, this new edition has been significantly updated and revised throughout to reflect current technology and industry practices, including shooting on DSLR cameras, in HD and on smartphones, new methods and channels of distribution, and much more. Key features and updates to the eighth edition include: - A focus on small-scale video production, involving a minimum amount of field equipment and a small crew, offering creative solutions for video producers with limited resources and personnel; - Discussions of HD and 4K technology/acquisition, virtual reality, LED lighting, DSLR, shooting with smartphones, and new online distribution channels; - Over 300 photos and line art, in full-color for the first time, illustrating production processes, technical issues, and equipment, and illuminating key aesthetic elements; - And an online resource with downloadable production planning documents, links to further online resources, production project exercises, and sample test questions. With over forty years of teaching and production experience, Ronald J. Compesi offers an up-to-date and essential introduction to the art of small-scale video production in field environments in the new edition of this groundbreaking text, in print since 1985"--Provided by publisher.